Modalities of intervention in advising management teams, teachers and other educational coordination bodies - Ramos Fresno, Mercedes (Avances en Supervisión Educativa, 2016)
This article aims to establish some notes identifying the counseling process that has been developing for educational inspection services . We will focus on advising management teams, teachers and Educational coordination bodies, bearing in mind that this is a triadic counseling, whose ultimate aim is to achieve the maximum development in students from the premises of quality and equity. We will also have in mind the implications for the organizational and professional development of teachers from the principles of participation and autonomy, and how it promotes teacher professional improvement, commitment to teaching practice and the necessary self-criticism to constantly evaluate, generating educational proposals flexible, through self-reflection.
Keywords: advice; participation; autonomy; school improvement; institutional support; professional development; organizational development; learning community